PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA TERBUKA MELALUI PENDEKATAN INVESTIGASI BAGI MAHASISWA PRODI PENDIDIKAN MATEMATIKA FKIP UMSU PADA MATAKULIAH TEORI BILANGAN - Nur 'Afifah; Ismail Hanif Batubara (MES: Journal of Mathematics Education and Science, 2019)
Abstract. The research objectives are: (1) Knowing whether the approach to the mathematical investigation can improve the ability to solve open mathematical problems; (2) Knowing how the level of activity of students and lecturers in learning through a mathematical investigation approach. This type of research is Class Action Research. The research subjects were Students of Mathematics Education FKIP UMSU Academic Year 2018/2019. The object of research is the ability of lecturers to manage student learning and activities in the implementation of learning and the ability of students to solve open mathematical problems through an investigative approach to material numbers. The results of the study show that (1) The approach to the mathematical investigation can improve students' mathematical problem-solving abilities; (2) The approach to the mathematical investigation can increase the level of student activity. From the results of the initial test the ability to solve open mathematical problems an average value of 3.17, the average value of student cycle I tests is 10.73 (56.66%) students who have the ability to solve open mathematical problems and average test scores the second cycle was 12 (83.33%) students who had the ability to solve open mathematical problems. Based on the conclusions above, this study suggests that consider the application of a mathematical investigation approach in order to improve the quality of mathematics learning.Keywords: Mathematical Investigation, Problem-Solving, Open-Mathematics.